Strength variation of pre-strain aluminium alloys (axial compression) due to isochronal annealing - Jantie, Beatrice Connie (2007)
Aluminium-Magnesium (Al-Mg) alloys have very good formability properties and have been used extensively for interior structural components of automotive body-in-white (BIW). The alloys in an annealed temper attain their strength through work hardening mechanism during press forming process. The strengthening mechanism is due to Mg atoms in solid solutions exerting dislocation drag during low temperature plastic straining. However, at elevated temperatures, high diffusivity of Mg atoms allows easy dislocations rearrangements which lead to reduction of mechanical strength (softening/thennal recovery). Furthermore, accumulation of stored energy in the dislocations substructures due plastic straining during press forming process also serves as a large driving force for thermal recovery. The two factors caused the components made out of Al-Mg alloy sheet to be susceptible to softening during paint bake cycle. This project will scientifically analysis those factors and makes suggestions how to mitigate the problem.